Estudio de prefactibilidad para la elaboración de una planta productora de pintura a base de dióxido de titanio y pigmentos minerales - Saenz Molfino, Alejandro Gabriel (2023)
The purpose of this document is to evaluate the economic, environmental and social profitability with respect to the implementation of a plant that produces paint based on titanium dioxide and natural pigments. After a market study, an unsatisfied demand was found, the target audience are people between 25 and 55 years old belonging to the socioeconomic level A, B or C, interested in painting the exterior of their home, contributing to the care of the environment. After choosing the district of Lurín as the place for the implementation of the business, and identifying the existing technology, we continued to answer the typical questions, such as, "How to produce?", "How much to produce?", " To whom to distribute? ”,“ How to organize the place? ”, among others, using industrial engineering tools and methods, such as the Process Operations Diagram, the Guerchet method, the supply chain, among others. Once the costs and expenses were identified, the economic and financial evaluation proceeded, where the calculations developed showed that the project is profitable, generating a profit after the implementation of said project. Likewise, new jobs were created, contributing to the development of society. Entrepreneurs are expected to become aware of the environmental impacts that companies have generated during the last decades, demonstrating that a project that ensures environmental and social care can also be economically profitable.